Adaptation to Blue Light in Marine Synechococcus Requires MpeU, an Enzyme with Similarity to Phycoerythrobilin Lyase Isomerases - Mahmoud, Rania M.; Sanfilippo, Joseph E.; Nguyen, Adam A.; Strnat, Johann A.; Partensky, Frédéric; Garczarek, Laurence; Abo El Kassem, Nabil; Kehoe, David M.; Schluchter, Wendy M. (Frontiers in Microbiology, 2017)
Marine Synechococcus cyanobacteria have successfully adapted to environments with different light colors, which likely contributes to this genus being the second most abundant photosynthetic microorganism worldwide. Populations of Synechococcus that grow in deep, blue ocean waters contain large amounts of the blue-light absorbing chromophore phycourobilin (PUB) in their light harvesting complexes (phycobilisomes). Here we show that all Synechococcus strains adapted to blue light possess a gene called mpeU. MpeU is structurally similar to phycobilin lyases, enzymes that ligate chromophores to phycobiliproteins. Interruption of mpeU caused a reduction in PUB content, produced impaired phycobilisomes and reduced growth rate more strongly in blue than green light. When mpeU was reintroduced in the mpeU mutant background, the mpeU-less phenotype was complemented in terms of PUB content and phycobilisome content. Fluorescence spectra of mpeU mutant cells and purified phycobilisomes revealed red-shifted phycoerythrin emission peaks, likely indicating a defect in chromophore ligation to phycoerythrin-I (PE-I) or phycoerythrin-II (PE-II). Our results suggest that MpeU is a lyase-isomerase that attaches a phycoerythrobilin to a PEI or PEII subunit and isomerizes it to PUB. MpeU is therefore an important determinant in adaptation of Synechococcus spp. to capture photons in blue light environments throughout the world’s oceans.